Indoor particulate matter measurement as a tool in the process of the implementation of Smoke-free Hospitals - Nardini, S.; Cagnin, R.; Invernizzi, G.; Ruprecht, A.; Boffi, R.; Formentini, S. (Monaldi Archives for Chest Disease, 2004)
Aim of the study: There are International and National standards that requires hospitals and health premises to be smoke-free. According to recent data from Italy and other European Countries, smoking is a widespread habit in hospitals. To get smoke-free hospitals in an Italian region, we have adopted the European Code for smoke-free hospitals, which sets standards and provides instruments for its implementation. According to the Code, whenever possible, each step towards a smoke-free hospital, should be shared by all staff. As a mean for achieving this goal, in our region the certification of single units as smoke-free units has been chosen. For getting the certification, besides implementing the Code, we planned to use ETS (Environmental Tobacco Smoke) monitoring, as ETS should not be present in hospitals. As a marker of ETS we have chosen Particulate Matter (PM), as it can easily be measured in real-time with a portable instrument and, when other - even outdoor - sources of combustion can be ruled out, it is an accurate detector of cigarette smoke. Here the first experience of measuring PM in hospitals for monitoring ETS and certificating smoke-free health premises, is described. Materials and methods: PM measurements were carried out without any previous notification in different areas of two Network hospitals of the Veneto Region, during a single working day. A real time laser-operated aerosol mass analyser was used. Several classes of PM (PM1, PM2.5, PM7, PM10, TSP Total Suspended Particles) were measured. Results: Outdoor PM levels were found to be repeatedly lower than the annual official limits of 65 mcg/m3 and around the 24 hour official limits of 15 mcg/m3 [15 to 20 mcg/m3, with an overall mean (Â±SD) of 17.8 (1.9)] throughout the whole day. Very good indoor air quality was found in the operating theaters and isolation department, where PM2.5 concentrations were much lower than outdoor levels [1.6 (0.9) and 5.9 (0.6) mcg/m3, respectively]. No increase in PM pollution was found in the surveyed medical offices, halls and waiting rooms where smoking was positively forbidden [PM2.5 concentrations of 14.8 (2.2) and 12.9 (1.1) mcg/m3] except in a medical office and in two coffee rooms for staff only where high PM levels were recorded [PM2.5 58.7 (29.1), 27.0 (10.6) and 107.1 (47.8) mcg/m3] and an offence of smoking restrictions could be proved. Conclusions: The measurement of PM in hospital for monitoring ETS proved to be both feasible and sensible. PM measurements with a portable instrument can be used both for controlling the compliance with rules or chosen standards and for educating staff about smoking related hazards, thus gaining consensus for the implementation of the tobacco control policy. In our experience, PM measurement can be used as an aid inside all actions designed by the European Code for smoke-free hospitals.